2011
DOI: 10.1242/jeb.053579
|View full text |Cite
|
Sign up to set email alerts
|

Desert ants benefit from combining visual and olfactory landmarks

Abstract: Visual cueAs a visual cue we used two pieces of black cardboard (each 10cm wide, 7cm high) that were placed adjacent to the nest entrance on the channel walls (Fig.1B) Accepted 20 December 2010 SUMMARY The desert ant, Cataglyphis fortis, uses both visual and olfactory cues to guide its return to the nest. The ants use vision-based path integration for long-distance navigation and memorize the visual and olfactory surrounding of the nest to finally locate the entrance. In the present study we investigated ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
87
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(90 citation statements)
references
References 25 publications
(33 reference statements)
1
87
1
1
Order By: Relevance
“…Currently, the nature of the olfactory or visual stimuli remains unknown and the degree to which successful homing relies on one or both sensory stimuli is inconclusive. Interestingly, work by Steck et al (2011) have demonstrated that desert ants (C. fortis) also use both olfactory and visual cues to guide their return routes to the nest. Following training with independent or combined cues, they found that ants learned the location of their nest more quickly with multimodal cues (Stecket al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the nature of the olfactory or visual stimuli remains unknown and the degree to which successful homing relies on one or both sensory stimuli is inconclusive. Interestingly, work by Steck et al (2011) have demonstrated that desert ants (C. fortis) also use both olfactory and visual cues to guide their return routes to the nest. Following training with independent or combined cues, they found that ants learned the location of their nest more quickly with multimodal cues (Stecket al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Past work has largely focused on the role of olfaction in tracking pheromone trails over short distances (Rosengren, 1977;Beugnon and Fourcassie, 1988), but there is evidence that non-pheromonal olfactory cues can also facilitate navigation. For example, the desert ant, Cataglyphis fortis, which was previously thought to rely solely on path integration and visual cues to navigate and find their nests, was recently found to use odor landmarks as well (Steck et al, 2009(Steck et al, , 2011. Additionally, German cockroaches, Blattella germanica, use path integration, visual landmarks, and olfactory cues to indicate the end of their path (Rivault and Durier, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…It complementarily uses odors while travelling (Wolf & Wehner 2000), and uses odors as an additional cue for finding its nest (Steck et al 2009). In fact, these ants use together visual and olfactory landmarks in an optimum combination (Steck et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…However, it seems likely that the importance of spatial learning for survival favors the simultaneous acquisition of redundant types of spatial information because it allows secondary cues to be used as backup when primary cues are unavailable (Shettleworth 2010). An increasing number of experiments support this idea in species ranging from insects (Wehner et al 1996;Steck et al 2011) to rodents (Lavenex and Schenk 1996;Rossier et al 2000;Shettleworth 2003, 2005).…”
Section: Introductionmentioning
confidence: 96%